LPLUNC1 reduces glycolysis in nasopharyngeal carcinoma cells through the PHB1‐p53/c‐Myc axis. Issue 3 (1st December 2022) - Oyang, Linda; Ouyang, Lei; Yang, Lixia; Lin, Jinguan; Xia, Longzheng; Tan, Shiming; Wu, Nayiyuan; Han, Yaqian; Yang, Yiqing; Li, Jian; Chen, Xiaohui; Tang, Yanyan; et al.
Abstract: Cancer cells prefer glycolysis to support their proliferation. Our previous studies have shown that the long palate, lung, and nasal epithelial cell clone 1 (LPLUNC1) can upregulate prohibitin 1 (PHB1) expression to inhibit the proliferation of nasopharyngeal carcinoma (NPC) cells. Given that PHB1 is an important regulator of cell energy metabolism, we explored whether and how LPLUNC1 regulated glucose glycolysis in NPC cells. LPLUNC1 or PHB1 overexpression decreased glycolysis and increased oxidative phosphorylation (OXPHOS)‐related protein expression in NPC cells, promoting phosphorylated PHB1 nuclear translocation through 14‐3‐3σ. LPLUNC1 overexpression also increased p53 but decreased c‐Myc expression in NPC cells, which were crucial for the decrease in glycolysis and increase in OXPHOS‐related protein expression induced by LPLUNC1 overexpression. Finally, we found that treatment with all‐trans retinoic acid (ATRA) reduced the viability and clonogenicity of NPC cells, decreased glycolysis, and increased OXPHOS‐related protein expression by enhancing LPLUNC1 expression in NPC cells. Therefore, the LPLUNC1‐PHB1‐p53/c‐Myc axis decreased glycolysis in NPC cells, and ATRA upregulated LPLUNC1 expression, ATRA maybe a promising drug for the treatment of NPC. Abstract : We investigated the roles and mechanisms of long palate, lung, and nasal epithelial cell clone 1 (LPLUNC1) in nasopharyngeal carcinoma (NPC) and found that LPLUNC1 could inhibit the glucose metabolism reprogramming via regulating the PHB1‐p53/c‐Myc axis, and small‐molecule drugs like all‐trans retinoic acid (ATRA) could restore the LPLUNC1 expression, resulting in inhibition of the growth and glucose metabolism reprogramming of NPC cells.